2020
DOI: 10.1002/hyp.13865
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation for multiple post‐wildfire hydrologic models

Abstract: Predictions of post‐wildfire flooding and debris flows are needed, typically with short lead times. Measurements of soil‐hydraulic properties necessary for model parameterization are, however, seldom available. This study quantified soil‐hydraulic properties, soil‐water retention, and selected soil physical properties within the perimeter of the 2017 Thomas Fire in California. The Thomas Fire burn scar produced catastrophic debris flows in January 2018, highlighting the need for improved prediction capability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 109 publications
(156 reference statements)
1
42
1
Order By: Relevance
“…Langhans et al (2016) demonstrated that plot‐scale infiltration rates were consistently higher than those in small watershed scales. Therefore, it is not surprising that the watershed scale K sh inferred here is smaller than that suggested by point‐scale measurements made shortly after other fires in the Transverse Ranges of southern California (Ebel, 2020; Kean et al, 2019; McGuire et al, 2018, 2019). However, our results in comparison with those of Rengers, McGuire, et al (2016) and Rengers et al (2019) suggest that the changes in effective saturated hydraulic conductivity are minimal when moving from small watersheds (<1.5 km 2 ) to large watersheds (~41 km 2 ).…”
Section: Discussioncontrasting
confidence: 58%
“…Langhans et al (2016) demonstrated that plot‐scale infiltration rates were consistently higher than those in small watershed scales. Therefore, it is not surprising that the watershed scale K sh inferred here is smaller than that suggested by point‐scale measurements made shortly after other fires in the Transverse Ranges of southern California (Ebel, 2020; Kean et al, 2019; McGuire et al, 2018, 2019). However, our results in comparison with those of Rengers, McGuire, et al (2016) and Rengers et al (2019) suggest that the changes in effective saturated hydraulic conductivity are minimal when moving from small watersheds (<1.5 km 2 ) to large watersheds (~41 km 2 ).…”
Section: Discussioncontrasting
confidence: 58%
“…These hydrological patterns did not appear to be affected by the fire. It is possible that fire led to an increase of surface runoff at the slope scale, as suggested by the occurrence of rill erosion in the burnt area ( Figure 3d) and as observed after a previous fire in the catchment (Ferreira, 1997); this has often been observed in burnt areas, both due to the presence of soil water repellency (Malvar et al, 2016) and the degradation of soil physical structure, decreasing hydraulic conductivity (Ebel & Moody, 2020;Varela, Benito, & Keizer, 2015). However, rip-ploughing might have broken the topsoil repellent layer, and limited hydrological connectivity might have prevented the effects of repellency from manifesting at the catchment scale, as observed elsewhere (Ferreira et al, 2008;Stoof et al, 2012).…”
Section: Hydrological Processesmentioning
confidence: 92%
“…These hydrological patterns did not appear to be affected by the fire. It is possible that fire led to an increase of surface runoff at the slope scale, as suggested by the occurrence of rill erosion in the burnt area (Figure 3d) and as observed after a previous fire in the catchment (Ferreira, 1997); this has often been observed in burnt areas, both due to the presence of soil water repellency (Malvar et al, 2016) and the degradation of soil physical structure, decreasing hydraulic conductivity (Varela et al, 2015;Ebel and Moody, 2020). However, rip-plowing might have broken the topsoil repellent layer, and limited hydrological connectivity might have prevented the effects of repellency from manifesting at the catchment scale, as observed elsewhere (Ferreira et al, 2008;Stoof et al, 2012).…”
Section: Hydrological Processesmentioning
confidence: 93%